17 Coronary angiography in a district general hospital. (18th May 2017) - Williams, Matthew GL; Fox, Danial; MacIver, David H; Dayer, Mark; Augustine, Katharine; Burn, Paul; Gosling, OE
Abstract : Introduction: CTCA is now an established diagnostic tool in the evaluation of chest pain, and with the recently up-dated NICE CG95 guidelines its use is likely to increase nationally. 1 We aimed to assess the demographics of our local patient cohort, protocol use, radiation dose and the accuracy and outcomes from our CT service. Methods: Demographic and outcome data was collected for a 17 month period from Jul 2015–Nov 2016. The CTCA result was compared with the invasive angiogram in patients who had both investigations. Results: 689 scans were performed with 95% for rule out of coronary artery disease. 8% of the scan protocols used were calcium scores only, 25% were prospectively ECG triggered spiral acquisition (FLASH), 60% prospective, 4% retrospective and 3% required more than 2 contrast scans. Mean BMI was?29±11 Kgm −2, median DLP 137 mGy*cm (IQR 87–230 mGy*cm), mean acquisition heart rate 61±21 bpm and median IV metoprolol dosage used was 8mg (IQR 0–20 mg). 98% of scans were diagnostic. 11% were referred on for angiography, 88% were recommended medical therapy and 1% were referred for MRI. There was 80% agreement with coronary angiography with 65% proceeding to intervention. 0% of patients who had a negative CTCA required subsequent intervention (before 15/11/16). Conclusion: Our real-world data demonstrates that CTCA in a district general hospital is an accurate and effective way to rationalise investigations, particularly in the management of coronary artery disease.